2015
DOI: 10.1371/journal.pone.0142877
|View full text |Cite
|
Sign up to set email alerts
|

An Interactive Text Message Intervention to Reduce Binge Drinking in Young Adults: A Randomized Controlled Trial with 9-Month Outcomes

Abstract: BackgroundBinge drinking is associated with numerous negative consequences. The prevalence and intensity of binge drinking is highest among young adults. This randomized trial tested the efficacy of a 12-week interactive text message intervention to reduce binge drinking up to 6 months after intervention completion among young adults.Methods and FindingsYoung adult participants (18–25 y; n = 765) drinking above the low-risk limits (AUDIT-C score >3/4 women/men), but not seeking alcohol treatment, were enrolled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
151
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 107 publications
(156 citation statements)
references
References 33 publications
5
151
0
Order By: Relevance
“…The ability to provide personalized feedback resulted in a reduction in alcohol consumption (Kypri et al, 2014), frequency of binge drinking (Voogt et al, 2014b), and drinking in a non-risky way (Suffoletto et al, 2015). Addressing the varying knowledge gaps of young people through an adaptable and tailored intervention is evidently effective; as this can help individuals better understand their own drinking behaviours and the associated health risks.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The ability to provide personalized feedback resulted in a reduction in alcohol consumption (Kypri et al, 2014), frequency of binge drinking (Voogt et al, 2014b), and drinking in a non-risky way (Suffoletto et al, 2015). Addressing the varying knowledge gaps of young people through an adaptable and tailored intervention is evidently effective; as this can help individuals better understand their own drinking behaviours and the associated health risks.…”
Section: Discussionmentioning
confidence: 99%
“…However, it was found that self-monitoring alone was not effective at decreasing alcohol consumption (Suffoletto et al, 2015).…”
Section: Text Messagementioning
confidence: 98%
See 3 more Smart Citations